Causes of shelter cats mortality in the Czech Republic - Vojtkovská, Veronika; Voslářová, Eva; Večerek, Vladimír (Veterinary and animal science, 2024)
Awareness of the causes of mortality in shelter cats can contribute to its effective reduction. The aim of this study was to investigate the causes of mortality in cat shelters in the Czech Republic, taking into account the age of the animals and their length of stay in the shelter facilities until natural death or euthanasia. A cooperation with two private no-kill shelters in the Czech Republic was established. The subject of the study were records of 3047 cats admitted to the selected shelters in the period from 2013 to 2023. A total of 357 (11.7 %) out of 3047 cats died or had to be euthanized in two monitored shelters. No significant difference (p > 0.05) in the cat mortality was found between the two shelters (11.5 % and 12 %). The median length of stay of cats in the shelter until death or euthanasia was 23 days. The highest mortality was recorded in the youngest cats (≤ 6 months). The most common causes of death or euthanasia of cats in both shelters were feline infectious peritonitis (21.6 %), panleukopenia (18.5 %) and upper and lower respiratory tract infections (17.5 %). Adult and older cats were significantly (p < 0.05) more prone to death due to renal failure and cancer than young animals and kittens. The results of the study contribute to the knowledge on the health of cat population in shelters in the Czech Republic and can serve as a basis for further work that will target mortality reduction strategies in at-risk categories.
Keywords: Death rate; Abandoned animal; Stray animal; Shelter